Organic and Symbiotic Fertilization of Tomato Plants Monitored by Litterbag-NIRS and Foliar-NIRS Rapid Spectroscopic Methods - Baldi, Elena; Toselli, Moreno; Masoero, Giorgio; Nuti, Marco (Journal of Agronomy Research, 2020)
Rapid analyses methods for the assessment of soil microbiota are lacking. In a commercial farm tomato plants were subjected to different fertilization strategies: 1. mineral Control (C); 2. Organic amendment (O); 3. Organic amendment + Micosat F © biofertilizer (OM). A first rapid method (Litterbag-NIRS) concerned hay litterbags coupled with a smart SCiOTM device. A second method (Foliar-NIRS) used the same device on the leaves. The plants showed positive responses to the amendment and biofertilization in the yield: C 60.5.1 t ha-1vs. 70.8 in O (+17%) and 74.2 in OM (+23% from C and + 5% (P 0.08) from O). The use of Litterbag-NIRS fingerprinting, completed with litterbags phenotyping and elaborated with a multivariate support vector machine classifier provided a similar knowledge to that obtained from microbial and chemical analyses of the soil. The reason for this response is that the analyses were embedded in the Litterbag-NIRS at medium-high precision. A polydromic function was hypothesized in order to disentangle the activities of different soil microbial populations from each other. The organic amendment delayed the functionality of the rapid r-strategist microbial populations, but at the same time activated slow k-strategists to intake the walls of the hay inside the litterbags. In this sense, the Litterbag-NIRS test can provide an effective “swamp” of the microbial fertility of the soil. Briefly, the Litterbag-NIRS coupled with Foliar-NIRS accounted for 95% of the average yield results, and both are therefore recommended for a rational assessment of microbial soil fertility.
Keywords: Amendment; Biofertilizer; Tomato; Litterbag-NIRS; Foliar-NIRS; SCiOTM